Ilusi demokrasi : kritik dan otokritik Islam - Saidi, Zaim, 1962- (Jakarta : Republika, 2007)
Criticism on Islam entering modern life towards capitalism
Daftar pustaka : p. 281-289
Keywords: Democracy -- Religious aspects -- Islam; Capitalism -- Religious aspects -- Islam